Nolatrexed dihydrochloride vs. doxorubicin, a clinical update of a multi-center randomized phase II study (014) in ethnic Chinese subjects with unresectable or metastatic HCC - Gallo, J. (Journal of clinical oncology, 2004)
4262 Background: Initial results of the original multi-center randomized Phase II study reported by Mok et al suggested that there was a 41% difference in the median survival of THYMITAQ (T) over doxorubicin (dox). We hereby present updated median survivals for the intent-to-treat (ITT) and evaluable populations within the same trial and a review of the patients' clinical characteristics in this particular trial.METHODS54 patients were randomized in a 2:1 fashion to receive either T (37) or dox (17), respectively. 44 subjects who completed 2 or more cycles of either drug were considered for the evaluable population. The clinical presentation of these patients is reviewed.RESULTSFor the ITT population, the median survival for the T arm was 19.8 wks and the dox arm was 14.8 wks, which represents a 34% increase in median survival in favor of T. The evaluable population for T produced a median survival of 23.4 wks compared to a median survival of 15.4 wks for dox, which represents a 52% increase in survival in favor of T. Of the 54 patients in the trial, 32 (59%) had cirrhosis, 22 of these in the T arm and 10 in the dox arm. In addition, 26 (48%) had portal invasion; 42 (78%) were hepatitis carriers.CONCLUSIONSAs noted in the previous communication of study 014 there is a difference in median survival in favor of T vs. dox. Although the p value (0.8519) on median survival was not significant; there was clinical benefit in terms of survival, particularly evident when the patient characteristics of each treatment arm are reviewed. Cirrhosis, portal invasion and hepatitis carriers have the worst outcomes in terms of survival in HCC. Regardless of these bad prognosis factors patients treated with T did better in terms of survival than those treated with dox (by 34% in ITT population and by 52% in evaluable population). The randomization in the current ETHECC (Evaluation of T in HCC) Phase III study is based on CLIP scores and Karnofsky PS which allows for an equal distribution of patients characteristics at randomization. The primary endpoint of ETHECC is overall survival in the treatment of unresectable HCC. [Table: see text].